Debt to Assets Ratio and Management Asset on Financial Performance: an Evidence of Chemical Companies in Indonesia Stock Exchange - Dolly Parlindungan Pardosi; Harlyn L Siagian (Ekonomis: Journal of Economics and Business, 2021)
This study aims to analyze the effect of Debt to Asset Ratio and Management Asset on Financial Performance in chemical companies listed on the Indonesia Stock Exchange. The population used in this study are chemical companies listed on the Indonesia Stock Exchange. The sample used in this study was 9 companies in 2015-2019, so that 36 research samples were obtained. In this study, Management Asset is measured using the Inventory Turnover proxy and Financial Performance using the Return on Assets proxy. Based on research, simultaneously, Debt to Asset Ratio and Management Asset have a significant effect on Financial Performance. While partially the Debt to Asset Ratio has an influence on the Return on Asset and Management Asset has no effect on the Return on Asset. Debt to Assets and Inventory Turnover ratios contributed 53.8% to Return on Asset.